Private Equity Transactions: Value Creation through Operational Engineering –~Evidence from Europe - Victor Heinrich (Junior Management Science (JUMS), 2023)
This paper investigates private equity value creation strategies through operational engineering. To examine this, I define a KPI framework typically favored by private equity firms. I apply propensity score matching to a dataset of European PE transactions compared to non-PE backed companies to study value creation. By applying a Difference and Difference regression setting and thereby controlling for two-way fixed effects, I can find strong evidence on PE value creation through operational engineering. This paper adds new insights to academia as (a) there are only few contributions using propensity score matching to examine PE value creation and (b) this paper is the first, to the best of my knowledge, to combine the approach of propensity score matching and Difference in Difference regressions, yielding highly significant results on the relevance of EBITDA margin improvement.
Keywords: 650; Private equity; Value creation; Operational engineering; Propensity score matching